Analisis Efektifitas Tepung Jamur sebagai Larvasida Aedes aegypti - Yasmin, Yekki; Fitri, Lenni; Bustam, Betty Mauliya (Jurnal Natur Indonesia, 2012)
This research is about effectivity analysis of two kinds of fungi i.e. Beauveria bassiana and Metharrizium anisopliae as Aedes aegyptilarvacide, it has been conducted at laboratories Zoology in Biology Department, Mathematics and Natural Sciences Faculty, Syiah KualaUniversity. Aims of this research were estimating maximum time storage of fungi powder as effective larvacide and the number of bacteriacolonies were found in water used for experiment. This research was used Completely Randomized Design (CRD). The experiments consistof two factors i.e kind and saving time of fungi. The result show that the longer the storage time of Beauveria bassiana the more ineffectiveit was as larvacide and the least fungi colonies were found. Metharrizium anisopliae on the other hand, the longer it was kept, the moreeffective it was as larvacide and the more fungi colonies were found.